2022
DOI: 10.1111/and.14453
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion from long‐acting testosterone replacement therapy to Natesto allows for spermatogenesis resumption: Proof of concept

Abstract: Long-acting testosterone replacement therapy (TRT) suppresses spermatogenesis.A short-acting TRT, Natesto, maintains spermatogenesis in some men. This study evaluated hormonal and semen parameters converting men from long-acting TRT to Natesto. Baseline hormones, again on long-acting TRT and 1 month after converting to Natesto, as well as semen parameters 3 months after converting to Natesto were assessed. Twenty-seven men were directly converted from longacting forms of TRT to Natesto. Mean duration on long-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Interestingly, estradiol levels were significantly lower while using the nasal gel compared with the long-acting TRT treatments. During the 3 months on the nasal gel, all 27 patients recovered spermatogenesis, with an average sperm concentration of 50.7 million/mL [26]. Nasal testosterone gel seems to be one of the best options for hypogonadal men wanting to preserve fertility, especially in those suffering from primary hypogonadism.…”
Section: (B) Nasal Testosterone Gelmentioning
confidence: 93%
See 1 more Smart Citation
“…Interestingly, estradiol levels were significantly lower while using the nasal gel compared with the long-acting TRT treatments. During the 3 months on the nasal gel, all 27 patients recovered spermatogenesis, with an average sperm concentration of 50.7 million/mL [26]. Nasal testosterone gel seems to be one of the best options for hypogonadal men wanting to preserve fertility, especially in those suffering from primary hypogonadism.…”
Section: (B) Nasal Testosterone Gelmentioning
confidence: 93%
“…One recent study looked at the direct conversion from long-acting testosterone replacement therapy to nasal gel therapy [26]. Five patients on transdermal gels, twenty patients on intramuscular testosterone cypionate, and two patients on subcutaneous pellets (with a mean age of 39 ± 8 years) for an average duration of 24.3 ± 19 months before conversion to the nasal gel treatment participated in the study.…”
Section: (B) Nasal Testosterone Gelmentioning
confidence: 99%
“…In men who are experiencing late-onset hypogonadism, therapy with TU seems safe, well tolerated, and a practical option. Most importantly, Kavoussi et al (2022) have established that fertility can be maintained in many men when they begin therapy with the latest short-acting intranasal androgen gel. (24) This applies even to men who have never been treated before or after the washing period of the long-working TRT method.…”
Section: Tu (Long-acting) and Short-acting Trt Mechanismmentioning
confidence: 99%
“…Additionally, it has been shown that most men who switch from long-acting TRT to Natesto can maintain their testosterone production, maintain reduced E2 levels, and have increased libido. (16) However, according to Bhasin et al (2018), the first diagnostic test should include a measurement of total testosterone levels in the morning of fasting using a proper and trustworthy test. The authors further suggest verifying the diagnosis by repeating the total T-level test taken in the early hours of the morning when the patient was fasting.…”
Section: Tu (Long-acting) and Short-acting Trt Mechanismmentioning
confidence: 99%